Clinical researchN-Terminal pro-Brain Natriuretic Peptide in decompansated ventricular septal defect - Baghdady, Yasser; Kamel, Yasser; Elwan, Amany (Archives of Medical Science, 2009)
Introduction: B-type natriuretic peptide (BNP) is a cardiac neurohormone secreted predominantly from the ventricles in response to increased ventricular pressure and volume overloads. There is little information available concerning plasma concentrations of BNP in children with ventricular septal defect (VSD), the most common congenital heart disease. The aim of the present study is to determine the plasma concentrations of NT-ProBNP in VSD patients presenting with cardiac decompensation and to correlate the level of NT-pro BNP with their clinical and echocardiography data. Material and methods: NT-proBNP was measured in forty five ventricular septal defects patients presenting with cardiac decompensation of various Ross Scores and the results were compared to thirty age and sex matched control group. The NT-proBNP level correlated with clinical and echocardiography data. Results: The mean value of NT-proBNP was significantly higher in patients with mild/moderate symptoms [Ross Class 2 and 3] (mean: 52.8 ±12.5 pg/ml), and patients with severe symptoms [Ross Class 4] (mean: 92.2 ±6.9 pg/ml) compared to the control group, (mean 14.7 ±3.6 pg/ml), p value < 0.0001. There was a positive correlation between Plasma NT-PROBNP level and left atrial dimension, left ventricular end diastolic dimension, pulmonary artery pressure, fractional shortening and weight affection with p < 0.01. Conclusions: NT-proBNP is elevated in VSDs with cardiac decompensation, it is correlated to clinical score and echocardiography parameters. It reflects pressure and volume loads to the pulmonary artery and right ventricle and may help to identify children with VSD and pulmonary hypertension that demands early intervention.